Testing small molecule analogues of the Acanthocheilonema viteae immunomodulator ES‐62 against clinically relevant allergens. (June 2016) - Janicova, L.; Rzepecka, J.; Rodgers, D. T.; Doonan, J.; Bell, K. S.; Lumb, F. E.; Suckling, C. J.; Harnett, M. M.; Harnett, W.
Summary: ES‐62 is a glycoprotein secreted by the filarial nematode Acanthocheilonema viteae that protects against ovalbumin (OVA)‐induced airway hyper‐responsiveness in mice by virtue of covalently attached anti‐inflammatory phosphorylcholine (PC) residues. We have recently generated a library of small molecule analogues (SMAs) of ES‐62 based around its active PC moiety as a starting point in novel drug development for asthma and identified two compounds – termed 11a and 12b – that mirror ES‐62's protective effects. In this study, we have moved away from OVA, a model allergen, to test the SMAs against two clinically relevant allergens – house dust mite (HDM) and cockroach allergen (CR) extract. We show that both SMAs offer some protection against development of lung allergic responses to CR, in particular reducing eosinophil infiltration, whereas only SMA 12b is effective in protecting against eosinophil‐dependent HDM‐induced allergy. These data therefore suggest that helminth molecule‐induced protection against model allergens may not necessarily translate to clinically relevant allergens. Nevertheless, in this study, we have managed to demonstrate that it is possible to produce synthetic drug‐like molecules based on a parasitic worm product that show therapeutic potential with respect to asthma resulting from known triggers in humans.